Limitations on the Supreme Court’s : Review of Legal Errors a Study within the Scope of Criminal Litigation - Mousa, Adnan; Al-Shimari, Kadhim (Journal of Legal Sciences, 2026)
The oversight exercised by the Court of Cassation over the trial judge includes the review of both the legal and factual assessments made by the judge. In both types of assessments, the Court of Cassation’s control is not absolute. While the general rule is that the Court of Cassation does not intervene in the factual assessment, except in exceptional circumstances, it can be stated that the general rule is for the Court to exercise control over legal assessments, with exceptions where this control is not applied. The situations in which the Court does not exercise control over legal assessments can be referred to as the limitations or constraints on the legal oversight carried out by the Court of Cassation. To address an error in law, it is necessary for the appellant to meet the requirements of standing and interest in the case. If either of these criteria is absent, the case cannot be considered, even if there is a legal error. Furthermore, the Court of Cassation must ensure not to harm the appellant when the appeal is filed by the appellant alone, without a counter-appeal. The Court cannot worsen the appellant’s position after they sought to improve it by filing the appeal. The Court is also bound by the grounds of the appeal, and new grounds raised for the first time in the appeal, which were not presented before the trial court, are not admissible.